Hemoglobinopatías en los países de la Cuenca del Caribe - Sáenz Renauld, German F. (Revista de Biología Tropical, 1988)
A review of hemoglobinopathies in the Caribbean basin, shows a clear association with race: In Costa Rica, evidence suggests two geographic origins for populations of African origin.